Polar Bear, Polar Bear, What Do You Hear? - Martin, Bill 1916-2004.; Carle, Eric (New York Henry Holt, 2010)
Zoo animals from polar bear to walrus make their distinctive sounds for each other, while children imitate the sounds for the zookeeper. Includes note to parents and teachers, and related activities.
Keywords: Animal sounds -- Juvenile fiction; Zoo animals -- Juvenile fiction; Stories in rhyme; Animal sounds -- Fiction; Zoo animals -- Fiction